2021
DOI: 10.1002/nafm.10628
|View full text |Cite
|
Sign up to set email alerts
|

Range Expansion and Factors Affecting Abundance of Invasive Flathead Catfish in the Delaware and Susquehanna Rivers, Pennsylvania, USA

Abstract: Flathead Catfish Pylodictis olivaris have been either intentionally or accidentally introduced into Atlantic Slope drainages extending from Florida to Pennsylvania and have quickly become established. In Pennsylvania, Flathead Catfish were first detected in the Schuylkill River at the Fairmont Dam in 1999 and in the Susquehanna River at Safe Harbor Dam in 2002. The species has since moved throughout the respective basins, with subsequent detections during 244 riverine surveys in these drainages. Fishway and el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…This pattern in nonnative catfish populations is seen with Blue Catfish I. furcatus (Fabrizio et al 2021;Hilling et al 2021;Nepal and Fabrizio 2021; all this special issue), bullheads Ameiurus spp. (Barabe 2021;Sikora et al 2021; both this special issue), Channel Catfish I. punctatus (Pennock et al 2018;Hedden et al 2021, this special issue), and Flathead Catfish Pylodictis olivaris (Hedden et al 2016;Massie et al 2018;Schmitt et al 2019;Smith et al 2021, this special issue), which was summarized by Montague and Shoup (2021, this special issue). The extent, ecology, and impacts of nonnative, invasive catfish populations are becoming better understood over time, and Fabrizio et al ( 2021) described the conflicts involved in managing invasive catfish.…”
Section: Ecology and Conservationmentioning
confidence: 98%
“…This pattern in nonnative catfish populations is seen with Blue Catfish I. furcatus (Fabrizio et al 2021;Hilling et al 2021;Nepal and Fabrizio 2021; all this special issue), bullheads Ameiurus spp. (Barabe 2021;Sikora et al 2021; both this special issue), Channel Catfish I. punctatus (Pennock et al 2018;Hedden et al 2021, this special issue), and Flathead Catfish Pylodictis olivaris (Hedden et al 2016;Massie et al 2018;Schmitt et al 2019;Smith et al 2021, this special issue), which was summarized by Montague and Shoup (2021, this special issue). The extent, ecology, and impacts of nonnative, invasive catfish populations are becoming better understood over time, and Fabrizio et al ( 2021) described the conflicts involved in managing invasive catfish.…”
Section: Ecology and Conservationmentioning
confidence: 98%
“…Impoundments result in a decline in juvenile Flathead Catfish habitat and can alter their development (Heimann et al 2007*). Flathead Catfish are able to migrate upstream from barriers, such as fishways, and can use dams as a staging area to forage before migrating (Raabe and Hightower 2014;Raabe et al 2019;Smith et al 2021). Flathead Catfish populations are unaffected by boat traffic disturbance in commercial navigation channels (Gutreuter et al 2006).…”
Section: Habitat and The Environmentmentioning
confidence: 99%
“…However, studies addressing the effects of dams on Flathead Catfish have shown inconsistent findings. Aadland (2015*) found that Flathead Catfish were absent above dams in Minnesota, but Smith et al (2021) found that Flathead Catfish have the ability to disperse despite the presence of dams. Lastly, there has historically been some question regarding whether Flathead Catfish populations should be managed riverwide or by river reach (Travnichek 2004).…”
Section: Movementsmentioning
confidence: 99%
See 1 more Smart Citation